The relationship between physical environment comfort and quality of worklife among supporting staff at UiTM Cawangan Pahang, Kampus Jengka / Raihanah Madihah Roslan - Roslan, Raihanah Madihah (Faculty of Business and Management, 2018)
The purpose of this study was conducted to examine the physical environment comfort towards quality of work life among supporting staff at UiTM Cawangan Pahang Kampus Jengka. There were three independent variables used for present study namely air conditioning, noise and lighting. The dependent variable for this study was quality of work life. This study used simple random techniques where the questionnaires being distributed to 70 supporting staff from different department in UiTM Cawangan Pahang Kampus Jengka. The result was analyzed by using SPSS to get the reliable result. Pearson Correlation is used as a measurement to investigate relationship between independent variable and dependent variable. The result found that all variables are reliable and have significant relationship between air conditioning, noise, and lighting with quality of work life. Based on the findings, noise has the most influence on quality of work life indicates that there was significant with a moderate degree of correlation (r=0.505, p=O.OOO).